Architectural Glory and Cultural fusion of Indo-Islamic and Bundeli Architecture during the Later Medieval Period - Shrivastava, Vinay (History Department, Semarang State University and Historian Society of Indonesia, 2021)
This article analyzes the glory and article fusion of Indo Islamic in South Asia during the Period of Pran Nath Temple Prana.Â In this research paper, after studying the primary source material available in Prannath temple, Panna, new facts have been compiled and analyzed from them, and new facts have been exposed. An intensive field survey has also been used in this research paper to shed light on the untouched points. Â Research result shows that: (1) In this region of Bundelkhand, the temple of Mahamati Prannath has become the center of religious tourism. Thousands of pilgrims have come over here in the Winter Festival in November every year after Dushahara for Sharad Purnima International Festival, (2) The temple of Prannath has become the architectural hub in Bundelkhand and provides so many primary sources to the researcher. Kuljam Swaroop, the pious Grantha of Pranami Sect, have preserved here in original form. This holy and religious grantha gives us valuable information for the regional history of Bundelkhand. (3) The temple of Prannath is a vast center of Communal harmony and Hindu-Muslim unity in this region (4) The Temple of Prannath provides a primary historical source regarding local history, history of Rulers of Bundelkhand, especially Maharaja Chatrasal, who was the disciple of Mahamati Prannath. The heritage of Bundeli and Islamic Architecture is very important for tourism objects.Artikel ini menganalisis kejayaan dan peleburan artikel Indo Islam di Asia Selatan pada Masa Prana Kuil Pran Nath. Dalam makalah penelitian ini, setelah mempelajari bahan sumber utama yang tersedia di Candi Prannath, Panna, fakta-fakta baru telah dikumpulkan dan dianalisis darinya, dan fakta-fakta baru telah terungkap. Sebuah survei lapangan intensif juga telah digunakan dalam makalah penelitian ini untuk menjelaskan poin-poin yang belum tersentuh. Hasil penelitian menunjukkan bahwa: (1) Di kawasan Bundelkhand ini, Candi Mahamati Prannath menjadi pusat wisata religi. Ribuan peziarah telah datang ke sini dalam Festival Musim Dingin pada bulan November setiap tahun setelah Dushahara untuk Festival Internasional Sharad Purnima, (2) Kuil Prannath telah menjadi pusat arsitektur di Bundelkhand dan menyediakan begitu banyak sumber utama bagi peneliti. Kuljam Swaroop, Grantha yang saleh dari Sekte Pranami, telah diawetkan di sini dalam bentuk aslinya. Grantha suci dan religius ini memberi kita informasi berharga untuk sejarah regional Bundelkhand. (3) Kuil Prannath adalah pusat luas kerukunan Komunal dan persatuan Hindu-Muslim di wilayah ini (4) Kuil Prannath menyediakan sumber sejarah utama mengenai sejarah lokal, sejarah Penguasa Bundelkhand, terutama Maharaja Chatrasal, yang murid Mahamati Pranath. Peninggalan Bundeli dan Arsitektur Islam sangat penting untuk objek wisata.